PERMINTAAN DAGING SAPI DI PROVINSI RIAU - Fadhlan Syihabuddin; Elinur; Sisca Vaulina (DINAMIKA PERTANIAN, 2019)
The husbandry sub-sector is a source of supporting energy for human needs, especially beef. Beef is a food commodity that has had an impact on improving public nutrition, especially animal protein. This study aims to analyze the development of beef demand and variables that influence it in Riau, the factors that influence beef demand in Riau Province, and the price elasticity, income elasticity, and cross elasticity of factors affecting meat demand beef in Riau Province. This research used the literature study. The data used in this research was data time series from 1999 to 2015. Data were analyzed using descriptive statistics, multiple linear regression, and elasticity. The results showed that the overall average development of beef demand, beef prices, chicken meat prices, rice prices, population income, and the population increased during the period. The factors that significantly influence the demand for beef were the price of beef and the price of rice. Meanwhile, the price of chicken meat, the income of the population, and the population had no significant to the demand for beef. The results of the elasticity calculation of demand showed that beef prices, rice prices, and population income were responsive to beef demand. This indicates that changes in beef prices, rice prices, and population income had a major impact on changes in demand for beef.